Wear Mechanisms Characterization Operating in Micro- and Nanoscale of the a-C:H Coating Implanted by Ag-Pt. (March 2018) - Janusz, M.; Major, L.; Kot, M.; Dyner, M.; Lackner, J.M.; Major, B.
Abstract: Wear mechanisms operating at the nanoscale may directly influence mechanical and biological properties of the advanced protective coatings used in industry. In the present research, the biomechanical properties of the advanced a-C:H coatings reinforced by different metallic crystallites have been characterized. The optimal biomechanical properties were found for the a-C:H implanted by AgPt crystallites. This coating has been selected for the detailed wear mechanism description at the nanoscale by transmission electron microscopy. Five zones of the coating deformation as a function of the distance from the centre of the maximum load during the wear process have been identified and described. Based on the bio-tribological properties, a-C:H coatings implanted by AgPt are the most promising for use in applications. Graphical abstract: Highlights: The optimum bio- tribological properties of the a-C:H + AgPt coating Five zones of the coating deformation as a function of the distance from the indenter Formation of the 'a-C:H bridged', or the 'openwork structure' during wear of the coating